The Effect of Aloe Vera Tea on Constipation Management And Safety of Fetal Growth - Arriza, Nurul; Usman , Andi Nilawati; Healthy Hidayanty; Ahmad , Mardiana; Risfa Yulianty; Irmayanti (Window of Health : Jurnal Kesehatan, 2024)
Constipation is one of the 60% of gastrointestinal discomforts in pregnancy. WHO (2018) states that 11-38% of pregnancies will experience constipation. It takes laxative substances that stimulate peristaltic movement of the intestinal wall, such as aloe vera. However, it contains a teratogenic component for pregnant women, namely aloin. The study aims to determine the effect of aloe vera tea as a treatment for constipation and test fetal weight growth's safety during organogenesis. Methods: This research is an experimental study, a laboratory pre-clinical study using a pre-post test randomized control group design in-vivo method. Against 24 pregnant mice constipated by induced oral extract of gambier 1 ml. Results: The control group intervention (Dulcolax 0.1 ml/20grBB) had a higher mean frequency than the aloe vera tea treatment. The results of the ANOVA test of 0.013<0.05 showed a significant difference between the four groups after five days. The category of the fastest onset of action of laxatives was shown in K3 (aloe vera tea dose of 0.2gr/20grBB) at 03:08 minutes compared to the control group (Dulcolax 0.1gr/20grBB) at 04:35 minutes. The ANOVA test of 0.000<0.05 showed a significant difference between K1, K2, K3 and K4. Based on the weight of the fetuses from the four groups was not significantly different (0.764>0.05). Conclusion: Dulcolax 0.1 ml and aloe vera tea 0.2gr/20grBB effectively increased the frequency of defecation in mice. Aloe vera tea 0.2gr/20grBB was very effective, with the fastest onset of laxative action compared to the control group. Aloe vera tea affects fetal growth in the form of a decrease in body weight at the highest dose of 0.4gr/20grBB. Suggestion: A dose of 0.2 grams of aloe vera tea is recommended to be converted to a human dose as an effective measure for treating constipation in pregnant women.